2014
DOI: 10.1007/978-3-319-07854-0_15
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic and Innovative Approach for Converting Pedagogical Text Documents to Visual Learning Object

Abstract: In this paper, we present a novel idea of converting pedagogical text documents to visual learning objects by automatically extracting nouns and semantic keywords from the text documents, and representing these keywords as a word cloud. A word cloud contains words that are weighted based on frequency, time, appearance, etc., depending on the concept they are used for. Each word in the word cloud would correspond to a visual representation of that word. A visual representation may contain drawings, figures, ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Imran et al [11] observe that visual learners are prevalent among students. This is one of the reasons that explains why images improve learning dramatically.…”
Section: Concept Maps In Visual Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Imran et al [11] observe that visual learners are prevalent among students. This is one of the reasons that explains why images improve learning dramatically.…”
Section: Concept Maps In Visual Learningmentioning
confidence: 99%
“…The author notes that meaningful learning often implies adding and rejecting some concepts to the concept map. Imran et al [14] convert a text into a word cloud by the following procedure: 1) to extract the terms with NLP techniques; 2) compute the semantic distance of the concepts to avoid natural language ambiguities; and 3) query the Internet to retrieve a semantic visual representation of the word [1].…”
Section: Concept Maps In Visual Learningmentioning
confidence: 99%
“…It has been widely accepted that engineering students prefer visual methods to perceive and, then, better process information 1,2,3 . In fact, it has been reported that visual aids can improve learning by up to 400%.…”
Section: Visual Learning Preference Among Engineering Studentsmentioning
confidence: 99%